Regreso del pasado: Madame Lynch y el imaginario paraguayo - Ramis, A. Gabriela (Latin American Theatre Review, 2010)
In the context of historical revisionism that characterized Latin American theater inthe last two decades of the twentieth century, Milton Schinca wrote Madame Lynch (1989).This essay looks at two political readings of Lynch’s marginality in Paraguayan society, andof her relationship to power as a way of highlighting social constructs. It does so by analyzingthe deliberate emphasis of the material conditions of Elisa Lynch, the function of her body,her use of visual and linguistic signs, the tension between power and marginality, and howmonologues work as an attempt to deconstruct the patriarchal view of Madame Paraguay.This leads to a reading of the playtext as an attempt to reconsider Uruguay’s responsibility inthe War of Paraguay (1865-1870). (AGR, Article in Spanish)